Exploring the electrochemical performance of nickel-zinc ferrite nanoparticles for supercapacitor applications - Kharat, Prashant B.; Somvanshi, Sandeep B.; Dawi, Elmuez A.; Mopari, Anuja M.; Bansod, Nitin H. (Journal of materials science. Materials in electronics, 2024)
In this research, nickel-zinc (Ni 0.5 Zn 0.5 Fe 2 O 4 ) nanoparticles of ferrite are tested to see whether they can function as electrodes in supercapacitors. The synthesized nanoparticles have been found to have a single-phase face-centered cubic structure, according to structural, morphological, and compositional analyses. The nanoparticles are confirmed to be in their typical structure since Fourier transform infrared examination shows that they contain no organic components. Analyses of the material's surface and magnetic properties suggest that it has superparamagnetic properties and a particular surface area of 42.26 m 2 g −1 , both of which are essential for improving energy storage efficiency. Reversible and steady redox behavior may be shown in cyclic voltammetry investigations as confirmed from the well-developed curve. Rapid charge–discharge response, potential plateaus, with overall stability indicate that these nanoparticles are well-suited for high-rate applications. The effect of the applied current density upon charge storage capacity is highlighted by a specific capacitance study showing an inverse connection between current density with capacitance. Analyzing the impedance and the Nyquist plot may provide light on the kinetics of charge transfer and the capacitive behavior. These results show that nickel-zinc ferrite nanoparticles may function well as supercapacitor electrodes. For the sake of designing and optimizing supercapacitors to satisfy future energy needs, this work adds to our knowledge of their electrochemical characteristics and energy storage capacity.